PERAN PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK KARAKTER DAN SPIRITUALITAS PESERTA DIDIK DI ERA MODERN - Yunita Sa'buran; Novia Andreas Padidi; Windy Fridelia; Krisma Kata; Kislen (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
This study aims to examine the role of Christian Religious Education in shaping the character and spirituality of students in the modern era. Technological developments, globalization, and changing values ​​in society bring various challenges to the world of education, particularly in the moral and spiritual development of the younger generation. In this context, Christian Religious Education plays a crucial role as a means of faith development that instills Christian values ​​such as love, honesty, responsibility, and concern for others. This study uses a qualitative approach with a library research method through a review of various literature sources relevant to the research topic. The results of the study indicate that Christian Religious Education plays a significant role in shaping the character and fostering the spirituality of students through integrative learning, teacher role models, and the development of spiritual activities within the educational environment. Despite facing various challenges in the modern era, strengthening contextual and reflective learning strategies can help Christian Religious Education remain relevant in shaping a generation with faith, character, and the ability to face the dynamics of modern life wisely.